THE GENDER PAY GAP AND ITS IMPACT ON WOMEN'S ECONOMIC EMPOWERMENT - Irshad Ahmad Reshi; Dr T. Sudha (RADJA PUBLIKA, 2023)
This research article aims to examine the gender pay gap and its impact on women's economic empowerment. The study uses both qualitative and quantitative research methods to explore the relationship between the gender pay gap and women's economic empowerment. The findings suggest that the gender pay gap has a significant impact on women's economic empowerment, limiting their financial independence and autonomy. The study also highlights the need for policy interventions and cultural changes to reduce the gender pay gap and promote women's economic empowerment